Perception on the Effectiveness of School Vegetable Garden Programme - T.G, Ajit; Mercykutty, M.J (Journal of Extension Education, 2020)
School vegetable garden is the practice of cultivation of vegetables in and around the school premises by the students. School vegetable garden programme is a promising tool that can teach cultivation of vegetable within the formal educational framework. It provides opportunities for young minds to understand the basic lessons of agriculture and develop an affinity towards it. A study was conducted among 180 student respondents among six schools by adopting the procedure of two stage random sampling, in Nenmara and Kollengode blocks of Palakkad district in Kerala. All the selected schools had functional school vegetable gardens and were practicing activities either through agriculture or nature clubs. The perceived effectiveness of school vegetable garden by students revealed that development of life skills was found to be the most important outcome. The constraints faced by students were more time spent for garden activities and difficulty in maintaining the garden during vacation.